An Overview Of Urea And Creatinine Levels In Patients With Chronic Kidney Disease And A History Of Hypertension Following Hemodialysis Therapy - Maichel Dwi Saputra Saputra; Oksita Asri Widyayanti; Suci Indah Budiarti (International Journal of Health Engineering and Technology, 2026)
Hypertension is both a cause and a consequence of Chronic Kidney Disease (CKD) and can contribute to the progression of kidney damage. Along with the decline in GFR, the incidence and severity of hypertension increase. When the kidneys are unable to perform the dialysis process, a treatment called hemodialysis (HD) is required to remove waste fluid accumulated in the toxic blood. A machine equipped with a semi-permeable filter (artificial kidney) is used to perform this therapy. The purpose of this study was to determine the profile of urea and creatinine levels in patients with chronic kidney disease (CKD) who had a history of hypertension, before and after undergoing hemodialysis at Level III Hospital 04.06.01 Wijaya Kusuma Purwokerto. Data analysis was performed using SPSS with a paired sample test. The urea levels before undergoing hemodialysis therapy ranged from a minimum of 70 mg/dL to a maximum of 288 mg/dL. After hemodialysis therapy, the urea levels ranged from a minimum of 53 mg/dL to a maximum of 277 mg/dL. Creatinine levels before undergoing hemodialysis therapy ranged from a minimum of 4.33 mg/dL to a maximum of 25.71 mg/dL. After hemodialysis, creatinine levels ranged from a minimum of 2.32 mg/dL to a maximum of 23.76 mg/dL. The statistical test results showed that the differences in urea and creatinine levels before and after hemodialysis were significant, with a p-value = 0.001.